ANALYSIS OF INBOUND AND OUTBOUND GOODS FLOW IN THE FROZEN FOOD WAREHOUSE OF UD. AL BARKAH, PALU CITY - Ramadan, Gilang; Duma, Yulius; Mashudie, Ritha Rahayu; Haerani, Haerani (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
This research aims to analyze the inbound and outbound flow processes at the frozen food warehouse of UD. Al Barkah in Palu City, Central Sulawesi. Using a qualitative approach with a case study method, the research was conducted in January 2025 with data collection techniques including direct observation, in-depth interviews with 12 key informants, and document analysis. The results show several constraints in UD. Al Barkah's warehouse management includes a time-consuming goods receiving process due to the continued use of physical checking and manual documentation, inadequate implementation of information technology in managing goods movement, and an unintegrated stock management system. This research recommends several improvements, including standardization of operational procedures, implementation of warehouse management information systems, optimization of warehouse layout, enhancement of quality monitoring systems, and development of human resource competencies. Implementing these recommendations is expected to improve operational efficiency, reduce the risk of errors in goods management, and enhance the quality of UD. Al Barkah's frozen food distribution services.